From “Dapo and Chabor” to “Cibai and Lanjiao” ——Analysis of the Semantic Field of Sensitive Words in Southern Min Language (从“查甫与查某”到“膣口与卵鸟” ——试析闽南语中的敏感词汇语义场) - TAN (é™ˆæ¯“åŸ¹), Yu Pei; CHOO (æœ±è’¨é›¯), Qian Wen (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2019)
Abstract Southern Min Language is a Chinese dialect with a non-Chinese language base. In Southern Min Language, there are many sensitive words that are not derived from Chinese, and can only be presented by transliteration or training. However, when most people study these sensitive vocabularies, they would try to figure out that what kind of relationship they have with ancient Chinese at the frist place, rather than consider whether they have a certain relationship with the ancient Minyue language. The modern Zhuang language has an inheritance relationship with the ancient Minyue language. Therefore, this article will link the modern Zhuang Language with the information of Southern Min language to explore the close relationship between them. Due to the particularity of these sensitive words , it is necessary to set up semantic fields when examining these sensitive words, distinguish them from other words, and focus on the correlation between the strong words in Z Tai-Kadai languages. 提要 闽南语是拥有非汉语底层的汉语方言，在闽南语中，有许多敏感词汇并非来源于汉语，也只能以音译或训读等方式呈现出来。然而多数人在研究这些敏感词汇时，首先揣摩的是它们与古代汉语存在着什么样的关系，而非考虑它们与古闽越语是否有一定的渊源。而现代壮侗语与古闽越语具有传承关系，因此本文将以现代壮侗语与闽南语的资料相联系，来探讨它们之间的密切关系。由于这些敏感词的特殊性，在考察这些敏感词时必须设立语义场，将它们与其他词汇区分开来，着重地观察壮侗语与闽南语中的敏感词之间的关联性。